In Vitro Anti-Candida albicans Mode of Action of Enterococcus mundtii and Enterococcus faecium - Svetoslav Dimitrov Todorov; Richard Weeks; Igor Popov; Bernadette Dora Gombossy de Melo Franco; Michael Leonidas Chikindas (Microorganisms, 2023)
Candida albicans is an important vaginosis causative agent, affecting several women worldwide each year. This study reports on two strains of lactic acid bacteria (Enterococcus mundtii CRL35 and Enterococcus faecium ST88Ch) expressing bacteriocin-like inhibitor substances (BLIS) active against C. albicans 1281. Both strains were γ-hemolytic and not affected by numerous antibiotics, contraceptives, and commercial drugs, suggesting safety for human use. The recorded antimicrobial activity of semi-purified BLIS was 25,600 AU/mL for E. mundtii CRL35 and 800 AU/mL for E. faecium ST88Ch. Treatment of BLIS with 1 mg/mL proteinase K resulted in complete loss of antimicrobial activity against Listeria monocytogenes ATCC 15313 and partial loss of activity against C. albicans 1281. The killing effect of the semi-purified BLIS on cell suspensions of C. albicans 1281 after 9 h of contact was dose-dependent: for E. mundtii CRL35, 400 AU/mL to 25,600 AU/mL caused 63.61% to 79.35% lysis, while for E. faecium ST88Ch, 200 AU/mL to 800 AU/mL caused 29.32% to 31.25% cell lysis. The effects of temperature, pH, and presence of the contraceptive Nordette-28 on the adsorption levels of the BLIS to C. albicans 1281 were also evaluated. Nordette-28 (10% or 20%) promoted increased adsorption of both studied BLIS to the cells of C. albicans 1281 at pH 5.0, while a minor effect was observed at pH 3.0. Different levels of aggregation between C. albicans 1281 and E. mundtii CRL35 or E. faecium ST88Ch were recorded, and optimal adsorption levels were recorded at 37 °C. Appropriate BLIS-producing strains can effectively contribute to the equilibrium of vaginal microbial status quo and reduce negative consequences from the development of C. albicans infections.